STUDI KELAYAKAN PENGEMBANGAN RUMAH SAKIT SUMBER HIDUP GEREJA PROTESTAN MALUKU DI KOTA AMBON - Steven Siaila; Jo Borolla; Meiske Wenno (Soso-Q : Jurnal Manajemen, 2019)
This study aims to determine the feasibility of developing a GPM Rumah Sakit Sumber Hidup (RSSH). To achieve the above objectives the Capital Budgeting Approach is used which includes the Calculation of Payback Period, Calculation of Net Present Value and Internal Rate of Return. In the Calculation used moderate, pessimistic, and optimistic conditions.The results obtained are that the mederat and optimistic scenario of the development effort is feasible to be carried out, whereas in the pessimistic scenario the effort to develop RSSH is not feasible in calculating the Payback Period and the internal rate of return. While the current value approach (NPV) is feasible.Based on the results of these calculations it can be concluded that the effort to develop RSSH is feasible to be carried out because the calculation results show profitable results. Keyword: RSSH Development Opportunity - Feasibility Analysis - Eligible To Be Done